Can Infant Massage Increase Baby Weight Being Cared for in the Perinatology Room of Fatmawati Hospital - Ayuda Nia Agustina; Ely Kinasih (JIKO (Jurnal Ilmiah Keperawatan Orthopedi), 2020)
Sometimes found babies who are hospitalized to experience weight loss or weight gain that are stuck. If if this problem lasts long it will affect baby's development and quality of life in the future. This study identified the effect of giving infant massage on the increase in baby weight during hospitalization. The study design was qualitative with multiple case design involving two infants and a mother who had the inclusion criteria: The baby did not have an intravenous fluid drip, the baby did not have congenital disease, had nursing problems, the risk of fluid volume deficiency, and the age of the baby was equal to or more than 6 days, and primipara. The research was conducted in March 2019, perinatology room of Fatmawati Hospital. The instruments used were in-depth interviews to explore the knowledge and skills of mothers caring for babies, flipcharts and videos to provide information on infant massage and using observation sheets to measure the mother's skills in infant massage. The results showed that there were differences in the knowledge and skills of mothers in doing baby massage, the average increase in baby weight was 30-45 grams per day. It is important that nurses provide education so that mothers can be skilled and confident while caring for their babies at home and increase the baby's weight while in the hospital.